Digital monitoring of the exercise's heart rate as a tool for determining personalized physical activity norms - Kovalev A.A. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to substantiate digital monitoring of the exerciser’s heart rate as a tool for determining personalized physical activity standards. Methods and structure of the study. Within the framework of the methodology for rationing physical activity of those engaged in health-improving physical culture, the totality of daily measurements of their heart rate is considered as a system of states of the human body. This solution is necessary when determining personalized physical activity standards based on daily heart rate data obtained using wearable devices. The problem of rationing physical activity has two contradictions: the mass distribution of wearable technologies and the insufficient use of their functionality to solve the problems of rationing health-improving physical activity; increasing the effectiveness of health-related activities and the lack of modern technologies for determining personalized standards. To solve the problem of personification of norms, it is proposed to use the theory of rank analysis, which is promising when studying daily non-Gaussian heart rate data obtained using wearable devices. The technology for rationing physical activity consists of the stages of preparation, collection and processing of data and development of proposals. Based on the results of the technology, based on the lower and upper limits and training potential, personalized values of physical activity standards are determined for three levels of training (beginner, intermediate, advanced). The recommendations obtained can be used as personal standards for physical activity and updated if necessary (after a month, quarter or year). Physical activity levels can be monitored using smart watches both during and after classes. At the same time, the obtained heart rate norms are personal and are suitable only for one person. Results and conclusions. The proposed system of states of the human body creates the prerequisites for determining personalized standards of physical activity and developing effective physical education and health programs for those involved in health-improving physical culture.